Colonic lavage in treatment of refractory Clostridium difficile infection: an adaptation of the Pittsburgh protocol. Issue 7 (14th July 2020) - Morgan, Maura; Farrell, Timothy; Ndubizu, Gordian U; Farrell, Timothy J
Abstract: Clostridium difficile infection (CDI) is a common nosocomial sequela in patients treated with antibiotics. Surgical intervention is indicated in fulminant cases. However, the mortality associated with total colectomy and end ileostomy is high. Previous reports have indicated that surgical intervention for severe complicated CDI with formation of a loop ileostomy leading to the diversion of fecal stream followed by colonic lavage can be beneficial in treating severe CDI. This procedure is known as the Pittsburgh protocol and has been reported to decrease the mortality and the need for a total colectomy in patients with severe complicated CDI. In this case, we present a 75-year-old female with refractory CDI. In her treatment, we adapted the Pittsburgh protocol and utilized a 20-French MIC gastrostomy tube to recreate the ileocecal valve and control the colonic lavage without retrograde flow.